Comparative paleogenomics of crucifers: ancestral genomic blocks revisited - Lysak, Martin A; Mandáková, Terezie; Schranz, M Eric (Current opinion in plant biology, 2016)
A decade ago the concept of the Ancestral Crucifer Karyotype (ACK) and the definition of 24 conserved genomic blocks was presented. Subsequently, 35 cytogenetic reconstructions and/or draft genome sequences of crucifer species (members of the Brassicaceae family) have been analyzed in the context of this system; placing crucifers at the forefront of plant phylogenomics. In this review, we highlight how the ACK and genomic blocks have facilitated and guided genomic analysis of crucifers in the last 10 years and provide an update of this robust model.
Keywords: Genomics; Polyploidy; molekulární evoluce; Evolution, Molecular; polyploidie; genom rostlinný; Genome, Plant; Brassicaceae; Arabidopsis; genomika